Real World Multicore Embedded Systems. - Moyer, Bryon (Elsevier Science, 2013)
This Expert Guide gives you the techniques and technologies in embedded multicore to optimally design and implement your embedded system. Written by experts with a solutions focus, this encyclopedic reference gives you an indispensable aid to tackling the day-to-day problems when building, optimizing and managing multicore embedded systems. Following an embedded system design path from start to finish, our team of experts takes you from architecture, through hardware implementation and software programming, to optimization and verification, including debug.